2009
DOI: 10.1080/09638280802306539
|View full text |Cite
|
Sign up to set email alerts
|

Lived experience of driving ability following stroke

Abstract: The findings indicate that driving is important and taken for granted even after stroke. To lose the ability to drive was unexpected and aroused strong feelings and reactions. The present study contributes to a deeper understanding of how people with stroke experience their driving ability and the evaluation process, which can be integrated in clinical procedures to help improve information, emotional support and clinical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 52 publications
1
37
0
Order By: Relevance
“…Settings of studies: community (n=34) [7],[52],[55][58],[60],[61],[63],[69],[71],[73],[75],[80],[83],[85][88],[90][94],[96],[99][101],[106],[110],[115][117],[119]; outpatient (n=5) [54],[62],[65],[74],[118]; care homes (n=3) [111][113]; hospital (n=6) [59],[68],[72],[81],[104],[107]; stroke units (n=8) [64],[66],[67],[76],[78],[79],[89],[95]; stroke medical centre (n=1) [108]; and mixed setting such as hospital and community (n=12) [53],[70],[77],[82],[84],[97],[98],[102],[103],[105],[109],[114]. Gender of participants: males and females (n=56) [7],[52],[53],[55][57],…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Settings of studies: community (n=34) [7],[52],[55][58],[60],[61],[63],[69],[71],[73],[75],[80],[83],[85][88],[90][94],[96],[99][101],[106],[110],[115][117],[119]; outpatient (n=5) [54],[62],[65],[74],[118]; care homes (n=3) [111][113]; hospital (n=6) [59],[68],[72],[81],[104],[107]; stroke units (n=8) [64],[66],[67],[76],[78],[79],[89],[95]; stroke medical centre (n=1) [108]; and mixed setting such as hospital and community (n=12) [53],[70],[77],[82],[84],[97],[98],[102],[103],[105],[109],[114]. Gender of participants: males and females (n=56) [7],[52],[53],[55][57],…”
Section: Resultsmentioning
confidence: 99%
“…Time since stroke (n=41) [7],[52],[55][58],[63][65],[68][71],[74],[78][80],[83][85],[87][89],[91][95],[97],[99][104],[107],[108],[110],[116][118] ranged from under 2 weeks to 16 years. Disability since stroke (n=39) [7],[54][56],[58],[61],[63],[65],[67][69],[71],[76],[77],[79][83],[85],[89]–[92],[95],[96],[99],[100],[102][104],[106],[108][110],[115],[117][119] was very variable. Ethnicity, when reported (n=13), varied between studies [71],[76],[79],[80],[82],[83],[87],[88],[90],[99],[103],…”
Section: Resultsmentioning
confidence: 99%
“…However, interviews with persons with stroke who underwent a driving evaluation revealed that the participants perceived the neuropsychological testing as insulting and pointless (13). The driving evaluation may be a very stressful situation for the client and we as occupational therapists need to start using tests with more face validity, like on-road tests.…”
Section: Introductionmentioning
confidence: 97%
“…Recent research does, however, indicate that persons who have driving difficulties post-stroke often also have limited awareness of their decreased ability to drive safely, and often continue to drive despite restrictions from the physician (45). Therefore, to efficiently convey alternatives to car driving among patients with CFLs and PFLs post-stroke, early initiated counselling based on comprehensive intervention strategies and use of awareness-training techniques are needed (2,19,20,45). However, current requirements for shorter hospital stays and rehabilitation periods do not facilitate individually tailored intervention strategies targeting aspects of outdoor mobility.…”
Section: Discussionmentioning
confidence: 93%
“…It is known that older car drivers generally adjust their driving behaviour to reduce risk exposure (5). Recent research does, however, indicate that persons who have driving difficulties post-stroke often also have limited awareness of their decreased ability to drive safely, and often continue to drive despite restrictions from the physician (45). Therefore, to efficiently convey alternatives to car driving among patients with CFLs and PFLs post-stroke, early initiated counselling based on comprehensive intervention strategies and use of awareness-training techniques are needed (2,19,20,45).…”
Section: Discussionmentioning
confidence: 97%